Utilization of Information and Communication Technology on the Learning Process in Elementary School - Nindya, Monica Isma Surya; Dafit, Febrina (International Journal of Elementary Education, 2022)
The problems so far are that schools have not utilized information and communication technology in class optimally. Teachers are only limited to using information and communication technology-based facilities and infrastructure for online learning. The purpose of this study is to be able to analyze the function of ICT for teachers in elementary schools and to be able to analyze the competence of ICT mastery that must be mastered by elementary school teachers, able to analyze the use of ICT as a source and medium of learning in elementary schools. This type of research uses a descriptive type of research. At the same time, the design of this study used a qualitative approach. This study intends to discuss facts and be able to tell things related to the use of ICT in carrying out activities in elementary schools. The research instrument in presenting the data is the researcher himself, who will determine the subject of the research and select information as a data source, collect data and compare the value of the data results and interpret the data and be able to analyze the data relate the results. Based on the results and discussion on ICT use, elementary schools have used ICT, both educators and students. In using ICT in elementary schools, educators need to pay attention to competencies in ICT mastery that elementary school teachers must master. Teachers use this ICT as a source and medium of learning in elementary schools.